2021
DOI: 10.1166/jbn.2021.3044
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Biodegradable Polymer Membrane for Guided Bone Regeneration in Bone Defect

Abstract: Guided bone regeneration (GBR) technique is most commonly used to treat alveolar bone defect. Polylactic acid (PLA) attracts much attention to utilize as a GBR membrane because it has relatively high mechanical strength and biodegradability. However, randomized controlled trials of PLA as a GBR membrane in animals were rare. The aim of this work is to observe the efficacy of polylactic acid membrane in guiding bone regeneration in Beagle canine alveolar bone defect restoration and to compare efficacy with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The degradation rate is consistent with the osteogenesis process. Histological observation of previous animal experiments showed that at 12 weeks postoperatively, the collagen membrane was completely degraded, while the PLA membrane maintained a relatively complete structure [28,35]; therefore, it can better protect new bone formation after bone grafting. Its good degradation rate prevents the invasion of soft tissue from interfering with bone healing, and its good supporting performance provides space for the growth of new bone units to obtain a good osteogenic thickness.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The degradation rate is consistent with the osteogenesis process. Histological observation of previous animal experiments showed that at 12 weeks postoperatively, the collagen membrane was completely degraded, while the PLA membrane maintained a relatively complete structure [28,35]; therefore, it can better protect new bone formation after bone grafting. Its good degradation rate prevents the invasion of soft tissue from interfering with bone healing, and its good supporting performance provides space for the growth of new bone units to obtain a good osteogenic thickness.…”
Section: Discussionmentioning
confidence: 97%
“…Owing to their advantages, such as simplicity, low cost, good biocompatibility, strong mechanical performance, controllable degradation time, and strong ability to guide tissue regeneration, PLA membranes have attracted much attention in the field of oral implantation. Previous animal experiments also confirmed that the degradation rate of the PLA membrane in vivo was slower than that of the Bio-Gide membrane, which can better match the repair rate of bone tissue [26][27][28].…”
Section: Introductionmentioning
confidence: 84%
“…Polylactic Acid (PLA) is a biodegradable material that can serve as a scaffold, and PLA-based composites are useful as temporary implants and membranes for osteosynthesis applications [7][8][9][10][11]. Specifically, PLA has gained much attention as a GBR membrane because of its handleability and biodegradability, and it has demonstrated that it is effective in this application of bone defects, favoring bone formation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although not discussed in this thesis, different biodegradable materials have also been developed and used for guided bone regeneration (GBR) in oral surgery [201][202][203][204][205] , in head and neck oncology 49 , and for pulsatile or delayed drug release 41 . In GBR, collagen is currently the most frequently used resorbable barrier membrane but membrane collapse into the defect can result in restricting the volume available for bone regeneration 206 .…”
Section: Final Remarks: a Broader Perspectivementioning
confidence: 99%
“…Biodegradable PLA membranes have been successfully used for GBR of alveolar bone properties 203 . In addition, biodegradable PLA membranes containing zoledronic acid have been developed for enhanced and faster bone formation during GBR 207 .…”
Section: Final Remarks: a Broader Perspectivementioning
confidence: 99%